The siting of public transport facilities in a predominately low to middle-income area, Klapmuts, on the outskirts of a metropolitan city, Cape Town - Wagner, Luke Phillip (Department of Civil Engineering, 2018)
The motivation for this study pertains to the Integrated Development Plan (IDP) for the Stellenbosch Municipal area identifying Klapmuts as an area in high need for formalising public transport infrastructure. The need for formalised public transport has arisen due to the envisaged future growth of Klapmuts, and the status quo of minibus-taxi operations in Klapmuts. The aim of this research was to critically evaluate relevant guidelines and policy documentation to aid in the siting of public transport facilities in a low to middle-income area, using Klapmuts, located on the outskirts of a metropolitan city, Cape Town as the study area. From a critical assessment of current practices, a warranting and siting practice for public transport and associated infrastructure was formulated which takes cognisance of the social and demographic characteristics of atypical low to middle-income area, as well as budgetary prioritisation and policy constraints imposed by the various planning and legislative entities to ensure that infrastructure is provided for in an efficient and effective manner. The warranting and siting practice developed in this dissertation serves to identify the public transport needs associated with affected groups including operators, passengers, and the community as a whole, and propose facilities and locations of facilities to cater for these needs. The methodology for the warranting and siting practice for minibus-taxi ranks and terminals, involves identifying the current needs for the study area, describing those considerations used to select a type of facility, and developing evaluation criteria which can quantitively compare sites in order to derive the most optimal alternatives for future investment.